Sarup phon thī samkhan čhāk kānsamrūat phāwa kānthamngān kh̨̄ong prachāk̨̄on, Ph̨̄o. S̨̄o. 2539 (Samnakngān Sathiti h̄æng Chāt, Samnak Nāyok Ratthamontrī, 1997)
Summary report of labor and office workers survey in Thailand, 1996.